How to Improve the Effectiveness of Monetary Policy in the West African Economic and Monetary Union - Kireyev, Alexei (IMF Working Papers; Working Paper, 2015)
The West African Economic and Monetary Union (WAEMU) is a currency union with a fixed exchange rate and limited capital mobility and, therefore, an independent monetary policy in the short run. The Central Bank of West African States (BCEAO) is conducting the single monetary policy with the main goal of preserving price stability and supporting economic growth. However, the effectiveness of its monetary policy remains low, with a weak reaction of market interest rates and inflation to BCEAO's policy actions. The paper concludes that, while the institutional setup and the instruments of monetary policy are adequate, the transmission mechanism of monetary policy remains constrained by liquidity management practices, shallow and segmented financial markets, and interest rate rigidities. To improve the effectiveness of monetary policy the BCEAO should be more proactive in determining the stance of fiscal policies, develop financial markets, and liberalize controlled interest rates. The BCEAO is undertaking important reforms in these directions.